A retrospective pilot study of correlation of cerebral augmentation effects of external counterpulsation with functional outcome after acute ischaemic stroke. Issue 9 (8th September 2015) - Xiong, Li; Lin, Wenhua; Han, Jinghao; Chen, Xiangyan; Leung, Thomas Wai Hong; Soo, Yannie Oi Yan; Wong, Lawrence Ka Sing
Abstract : Objective: External counterpulsation (ECP) is a non-invasive method used to augment cerebral blood flow of patients with ischaemic stroke via induced hypertension. We aimed to explore the correlation between the cerebral blood flow augmentation effects induced by ECP and clinical outcome after acute ischaemic stroke. Methods: We retrospectively analysed our ECP registry of patients with ischaemic stroke who were enrolled within 7 days after stroke onset. Bilateral middle cerebral arteries of patients were monitored using transcranial Doppler (TCD). Flow velocity changes before, during and after ECP were, respectively, recorded for 3 min. The cerebral augmentation index (CAI) was the increase in percentage of the middle cerebral artery mean flow velocity during ECP compared with baseline. TCD data were analysed based on the side ipsilateral or contralateral to the infarct. The modified Rankin Scale (mRS) (good outcome: mRS 0∼2; poor outcome: mRS 3∼6) was evaluated 6 months after the index stroke. Results: 72 patients were included (mean age, 63.8±10.7 years; 87.5% males). At month 6 after stroke onset, univariate analysis showed that the National Institutes of Health Stroke Scale at recruitment was significantly higher and ECP therapy duration was longer in the poor outcome group, while the ipsilateral CAI was significantly lower in the good outcome group than that in the poor outcome group (3.71±4.94 vs 7.73±7.66, p=0.044). Multivariate logistic regression showed that ipsilateral CAI was independently correlated with an unfavourable functional outcome after adjusting for confounding factors. Conclusions: The higher degree of cerebral blood flow velocity augmentation on the side ipsilateral to the infarct induced by ECP is independently correlated with an unfavourable functional outcome after acute ischaemic stroke.